Johanna Hanink, The Classical Debt: Greek Antiquity in an Era of Austerity - Plantzos, Dimitris (Historein, 2019)
Review of Johanna Hanink, The Classical Debt: Greek Antiquity in an Era of Austerity. Cambridge: Belknap Press of Harvard University Press, 2017. 352 pp.